A human antibody of potent efficacy against SARS-CoV-2 in rhesus macaques showed strong blocking activity to B.1.351. Issue 1 (1st January 2021) - Gu, Chunyin; Cao, Xiaodan; Wang, Zongda; Hu, Xue; Yao, Yanfeng; Zhou, Yiwu; Liu, Peipei; Liu, Xiaowu; Gao, Ge; Hu, Xiao; Zhang, Yecheng; Chen, Zhen; et al.
ABSTRACT: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which causes coronavirus disease-2019 (COVID-19), interacts with the host cell receptor angiotensin-converting enzyme 2 (hACE2) via its spike 1 protein during infection. After the virus sequence was published, we identified two potent antibodies against the SARS-CoV-2 receptor binding domain (RBD) from antibody libraries using a phage-to-yeast (PtY) display platform in only 10 days. Our lead antibody JMB2002, now in a Phase 1 clinical trial (ChiCTR2100042150), showed broad-spectrum in vitro blocking activity against hACE2 binding to the RBD of multiple SARS-CoV-2 variants, including B.1.351 that was reportedly much more resistant to neutralization by convalescent plasma, vaccine sera and some clinical-stage neutralizing antibodies. Furthermore, JMB2002 has demonstrated complete prophylactic and potent therapeutic efficacy in a rhesus macaque disease model. Prophylactic and therapeutic countermeasure intervention of SARS-CoV-2 using JMB2002 would likely slow down the transmission of currently emerged SARS-CoV-2 variants and result in more efficient control of the COVID-19 pandemic.